HYGIENE ANALYSIS OF EDUCATIONAL INSTITUTIONS AND SPORTS FACILITIES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article gives recommendations on the sanitary and hygienic requirements for sports facilities for educational institutions, the main parameters of gyms, the choice of materials for finishing, the main dimensions of the pools and the organization of training.